2016
DOI: 10.1002/jso.24260
|View full text |Cite
|
Sign up to set email alerts
|

Modified pectoralis major myocutaneous flap for the total glossectomy defects: Effect on quality of life

Abstract: Modified technique of reconstruction with PMMC in total glossectomy is a viable option with minimal functional morbidity. Quality of life in terms of tracheostomy and feeding tube dependency is minimal. J. Surg. Oncol. 2016;114:32-35. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This allowed the use of thin free flaps (eight suprafascial‐ALT and six RFF; 82% of cases), which have good pliability and versatility; they restore almost half of the tongue volume loss while preserving its complex mobility . In case of contraindications for microsurgery, accordingly to literature, pedicle flaps such as PMMC and FAMM, or submental artery island flap (SAIF) might be considered as good reconstructive options for this type of defect …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed the use of thin free flaps (eight suprafascial‐ALT and six RFF; 82% of cases), which have good pliability and versatility; they restore almost half of the tongue volume loss while preserving its complex mobility . In case of contraindications for microsurgery, accordingly to literature, pedicle flaps such as PMMC and FAMM, or submental artery island flap (SAIF) might be considered as good reconstructive options for this type of defect …”
Section: Discussionmentioning
confidence: 99%
“…24,39,40 In case of contraindications for microsurgery, accordingly to literature, pedicle flaps such as PMMC and FAMM, or submental artery island flap (SAIF) might be considered as good reconstructive options for this type of defect. [41][42][43][44] In comparison to type 2 defects, patients with type 3 defects require more extensive and complex resection, involving more than 50% of tongue volume ("Extended hemiglossectomy"). In other words, multiple tongue subunits are removed, sometimes requiring mandibulotomy or lip split for access, thus affecting form and mobile function considerably.…”
Section: Discussionmentioning
confidence: 99%
“…The standard reconstruction approach for many head and neck abnormalities in the modern era is free tissue transfer. However, due to its speed, the PMMC is still a viable option to consider when vascularized soft tissue coverage is needed (Gangiti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…PMMC flaps requires minimal expertise and can be modified based on the dimensions required and is the workhorse flap in the head and neck reconstruction and can be easily harvested. [ 23 ] Studies by Hsing et al , Xiao et al , and O’Neill et al . showed that PMMC had no significant difference in pain, appearance, swallowing, chewing, and other functional aspects when compared with free flaps, ALT, and FRAFF respectively.…”
Section: Discussionmentioning
confidence: 99%